"Ex-tinto": deconstructing black authorial poetics - Souza Antero, Rodrigo Augusto de (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
This article presents a deconstruction (Ileana Diéguez, 2018) of the authorial creative process ex-tinto (2018), developed in the Graduate Program in Arts at the Escola de Belas Artes of the Universidade Federal de Minas Gerais. This deconstruction was grounded in autobiographical research, including an artist-researcher diary to produce escrevivências (Conceição Evaristo, 2020) of a trilogy of Black performances titled Projeto Córpe. Ex-tinto, the trilogy’s final work, investigates the materiality of white disposable cups, which are configured as a “white mask” (Frantz Fanon, 2008), through a masking process that denounces and exposes structural racism and whiteness.